Analisis Tentang Teori Permintaan dan Penawaran dalam Ekonomi Global - Muhammad Ash-Shiddiqy (Journal Actual Organization of Economic, 2025)
Supply and demand theory is a fundamental concept in economics that affects the dynamics of world markets. The purpose of this study is to analyze the interaction of demand and supply and its impact on the price and quantity of goods, analyze how global factors such as international trade, exchange rate fluctuations, and macroeconomic policies affect the supply and demand mechanism and analyze the impact of supply and demand on the global economy. To achieve these objectives, this research uses a literature review by collecting and analyzing information from various books and journals. The research results are as follows: Global factors such as international trade, exchange rate fluctuations, and macroeconomic policies affect the supply and demand mechanism, supply and demand affect global economic growth. The study concludes that adaptive economic policy management and international cooperation are key to addressing the challenges of maintaining global market stability.